Urban Tourism Development Through Low Impact Development (LID) Towards Green-Tourism - Wiwik Setyaningsih; Tri Yuni Iswati; Sri Yuliani (Bandar Lampung University (UBL), 2014)
World Tourism Organization (WTO), is one of the global issues on the international scene, because of the impact of tourism activities on the development and improvement of the economic, social, cultural and environmental quality to the green-tourism. It is based with the Surakarta- city as tourism and cultural city towards the eco-city culture.The aim of the research, will focus on urban tourism and build formulation development through low impact development, in the realization of green-tourism. It is based on explorative descriptive method combined with the mapping spatial of potential physical character (layout, building, and environment), included cultural, social and economic effects of tourism. The location of the research is Kauman urban settlement having a valuable unique and local potential and also its activities which are still exist right now.The result of the research, shows that the existence layout and environment of Kauman urban settlement has not been handled optimally. Moreover, it tends to lose its characteristics because it isn’t protected. Therefore, structuring a tourist area that emphasizes the use of natural and cultural resources wisely by prioritizing continued existence and local knowledge to minimize the negative impacts of tourism on the environment. The concept is conceived for all parties concerned agreed that the application does not give rise to contradictions between the various interests, useful as a guide to apply sustainable development of urban tourism is paying attention to the environment and local communities.The conclusion, that purposed to fulfill the formulated of urban tourism development policies that are environmentally friendly and sustainable.